(untitled) (Eurasian Research Bulletin, 2025)
This article examines the role of the educational services market in the context of the digital transformation of society and the economy. It examines key trends in the digitalization of the education system, the functioning of educational institutions in this new environment, and the impact of digital technologies on the quality and accessibility of educational services. The challenges and prospects for the development of the education market in the digital environment are identified.